Identification of Steroids in Wheat Bran - FENG, XU; JIANG, DONG; SHAN, YU; DAI, TINGBO; JING, QI; DONG, YUNFA; CAO, WEIXING (Asian Journal of Chemistry, 2010)
To well utilize wheat product and improve its commercial value, nutritionally and medically, foundational steroids in wheat bran were identified in the present study. Steroid components in wheat bran were extracted with hexane and identified based on direct comparison with mass spectral data supplied by Finnegan. Total seven sterol 3-ols and twelve steroidal 3-ones were detected by GC-MS, which were identified for the first time in wheat bran, and eight minor steroids, i.e., 24-ethyl-5α-cholestan-22-en-3-one, 24-ethyl-5α-cholestan-'24(28)-en-3-one, spinasteron, 4-methyl-24-ethylcholest- 4,24(28)-dien-3-one, 4-methyl-24-ethylcholest-4,22-dien-3-one, 4-methyl-αa-cholestan-3-one, 24-ethyl-5α-cholestan-24(28)-en-3β-ol, 24-ethyl-5α-cholestan-22-en-3p-ol, were first reported in wheat. Based on Takatsuto's report, biosynthetic relationships of steroids with brassinosteroids were presumed and biosynthetic pathway of steroids in wheat grain was discussed.